EDUCATION, MÉDIAS & PUBLICS EN ALGÉRIE - Akka, Zakaria (European Scientific Journal, ESJ, 2015)
Served by their strategic position at the crossroads of social exchanges, due to the slow but steady decline in the role of traditional institutions such as religion, family and school, and with the rapid technological development experienced by the information and communication sector, the media have acquired today a remarkable influence in the process of socialization and education of the young. But while the action of the traditional actors mentioned above provide direction and guidance, that of the media, as a whole, follow a logic of consumption that is at odds with the quality requirements of the general interest. As such, the Algerian user, in particular, on the one hand is weighed down by the mediocrity of the local media and cultural output and on the other hand, suffers the brunt of the onslaught of globalized and often inadequate digital content that the Internet pours out continuously. As a result, the public, especially the young, loses its bearings and becomes easily manipulated. By empowering him and strengthening his critical awareness and capacity for discernment, media literacy would help him develop a citizenship that is democratic, active, participative and responsible at the same time.